Concrete Brick Wasted Material Substitution Performance: Role of Fly Ash, Mixture Composition, and Compressive Strength - Rul, Syahrul; Amir (Jurnal Teknik Sipil dan Perencanaan, 2025)
The optimization of wasted materials, especially local fly ash, provides space to be used as a construction material with the potential to partially replace cement without reducing the mechanical strength of concrete bricks to a proportion of 20%. Using waste materials like fly ash will provide economic value, environmental sustainability, and strength and durability. A mixture of local sand, PCC cement, and fly ash material is 0%, 5%, 10%, 15%, and 20%. Concrete bricks or commonly called paving blocks are products with sand, water, and cement compositions, as well as waste materials, the installation and maintenance of concrete bricks is very easy and can be formed with various variations that provide aesthetic aspects, the mechanical parameters of concrete bricks are 3, 14, and 28 days old compressive strength tests with a total of 75 samples with a quality classification D. Weight ratio 1:4 cement,  sand and cement water 0.58. The weight of the cement determines the amount of fly ash. The performance of fly ash waste-substitution concrete bricks by 10% produced a quality of 11,674 MPa in 28 days.